TINGKAT DAYA TAHAN KARDIOVASKULAR SISWA SSB NEGAROA - Yullianto, M Dwi; Hidayat, Syarif; Kusuma, Ketut Chandra Adinata (Journal of Sport and Exercise Science, 2020)
This study aims to determine the level of cardiovascular endurance of SSB Negaroa students in 2020. Subjects in this study were SSB Negaroa U-15 students, amounting to 15 people. The method used is a survey with test and measurement data. The instrument used to determine the level of cardiovascular endurance is the Multistage Fitness Test (MFT). The results showed there were no students who won the special category and the category was very good (0%), in the good category there were 2 students (13.33%), in the medium category there were 2 students (13.33%), in the poor category there were 1 students (6.67%), in the very poor category there were 10 students (66.67%). Based on these data, the highest frequency is very bad category. So it is recommended for trainers to make training programs more attentive to efforts to improve cardiovascular endurance but also without ignoring technical or tactical training. As for students to make these results as guidelines and tools to motivate themselves to have better cardiovascular endurance.